A Vietnamese Case Study of Artificial Intelligence in K-12 Education - Nguyen Thi Thao Ho; Ly Thi Khanh Pham (Acta Pedagogia Asiana, 2026)
Artificial intelligence (AI) in K-12 education has the potential to alter learning experiences through individualized instruction, adaptive learning systems, and intelligent tutoring systems. It uses AI's data analysis skills to deliver personalized learning routes suited to each student's needs. AI technologies can evaluate student progress in real-time, provide timely feedback, and find areas for growth. Furthermore, AI-powered educational systems may assist instructors by automating administrative work, allowing for more emphasis on student connection and instructional innovation. However, issues like data protection, equitable access to technology, and the requirement for teacher and student training in AI integration must be solved before AI can fully realize its promise in K-12 education. This study demonstrates a Vietnamese Xschool employing AI for grades 1, 2, 3, and 7. Notably, the case study highlights the key challenges faced in AI implementation in practice and provides practical implications for the effectiveness of AI implementation for primary and secondary schools.